1998
DOI: 10.1097/00007890-199805270-00008
|View full text |Cite
|
Sign up to set email alerts
|

Histological Features Predictive of Recurrence of Primary Biliary Cirrhosis After Liver Transplantation

Abstract: The risk of PBC recurrence is real (8.7%). The presence of plasma cells in the portal infiltrate seems to be an early marker of recurrence of PBC in patients transplanted for this indication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
38
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 17 publications
1
38
0
Order By: Relevance
“…Plasma cell-rich periportal hepatitis may be an early marker predictive of later PBC recurrence. 82 Nonspecific lobular findings include mild spotty hepatocyte apoptosis, slight sinusoidal lymphocytosis, mild nodular regenerative hyperplasia, and Kupffer cell granulomas.…”
Section: Recurrent Diseases and New-onset Diseasesmentioning
confidence: 99%
“…Plasma cell-rich periportal hepatitis may be an early marker predictive of later PBC recurrence. 82 Nonspecific lobular findings include mild spotty hepatocyte apoptosis, slight sinusoidal lymphocytosis, mild nodular regenerative hyperplasia, and Kupffer cell granulomas.…”
Section: Recurrent Diseases and New-onset Diseasesmentioning
confidence: 99%
“…For example, Sebagh 13 described the histologic features in the allograft of 69 patients grafted for PBC and 53 patients grafted for alcoholic and metabolic liver disease; all had been followed for over 1 year. Histologic features of PBC (such as nonsuppurative, destructive cholangitis; mixed portal cell infiltrate; and ductopenia) were present in 6 of the 69 patients grafted for PBC and none of the metabolic/alcohol group.…”
Section: Histologic Evidence For Recurrence Of Pbc In the Allograftmentioning
confidence: 99%
“…Some centers (including our own in Birmingham) that have reported in preliminary studies that there was no evidence for recurrent PBC have later reached different conclusions. 11,13,20 Thus, Dubel et al 5 reported in 1995 on the liver histology of 16 patients transplanted for PBC and followed for at least 4 years; 6 patients developed histologic features of chronic active hepatitis (related to HCV infection in 5 and HBV infection in 1) and 1 patient had mild steatosis 2 years after transplantation; the other 9 patients had either no, or else a mild, transient portal tract infiltrate, and none had features of recurrent PBC. All patients were maintained on triple immunosuppression with corticosteroids, azathioprine, and ciclosporin.…”
Section: Why Do All Reports Not Agree On Recurrence?mentioning
confidence: 99%
“…5 It is now well established that PBC may recur in the allograft in some patients. [6][7][8] In this study, we have reviewed our clinical experience with 400 consecutive PBC patients who underwent a total of 416 liver transplantations. The aims were to determinate the actuarial patient and graft survival, reasons for graft loss and death, to determine how referral and transplant patterns have changed with time and to determine the incidence of recurrent disease.…”
mentioning
confidence: 99%